The macro-north-northeastern Peru: land and archaeological data - Bueno Mendoza, Alberto (2013)
The work focuses on the study macroregional northern territorial continuity factor. The landforms identified include differences and similarities in relation to certain landscapes featuring the various realities. The man and his organizations have occupied these territories in order to solve their needs and attract wildlife resources for solving everyday and permanent establishments.